Pemenuhan Kebutuhan Air Bersih Di Desa Pondok Panjang Kecamatan V Koto Kabupaten Mukomuko - YUWANDI, DEFRI; Rianto, M.Pd, Slamet; SE, M.Si, Nefilinda (Pendidikan Geografi, 2014)
ABSTRAK This research aim to know and analyse data about 1). Way of society in accomplishment of clean amount of water required in Long Countryside Maisonette of District Of V Koto Sub-Province of Mukomuko 2). Mount knowledge of society in accomplishment of clean amount of water required in Long Countryside Maisonette of District Of V Koto Sub-Province of Mukomuko 3). Mount earnings of society in accomplishment of clean amount of water required in Long Countryside Maisonette of District Of V Koto Sub-Province of Mukomuko.This Research type is descriptive. Population in this research is entire all KK exist in Long Countryside Maisonette of  District Of V Koto Sub-Province of Mukomuko amounting to 119 KK. Sampel in taking totally sampling so that research sampel amount to 119 KK.Result of this research is found: 1). From facet of is way of Society in fulfilling everyday requirement of a more regular use well water ( 63,87%). Water which is often used for MCK is river water. A more regular use well water from at river water ( 65,55%). Natural society of moment diarrhoea consume well water ( 42,01%). In fulfilling clean amount of water required of society do not use water of Company Of Area Drinking Water ( PDAM)     (60,50%). 2). From facet knowledge of society know difference of clean water with water which do not cleanness ( 56,30%). Society know effect of which is generated by using river water for bath ( 73,10%). Society less is knowing of condition for water which is clean           (41,17%). Society know that with consuming dirty water can cause disease ( 65,54%). 3). From facet earnings of Amount earnings in 1 months of work of fundamental is > Rp 1.000.000-Rp 1.500.000 ( 48,73%). Amount of expenditure in 1 months to fulfill requirement of fundamental is > Rp 750.000-Rp1.000.000 ( 52,94%). Within per month accept labourage ( 78,99%). Amount of responsibility in family 4 people ( 45,37%). Earnings do not be used in subscribing to water of PDAM ( 47,05%).